Evaluasi Pembelajaran di Masa Pandemic Covid-19 di Lembaga Pembinaan Khusus Anak (LPKA) Kelas II Jakarta - Eka Rista Harimurti (Syntax Idea)
This article aims to evaluate the implementation of learning during the Covid - 19 pandemic which was organized by the Jakarta Class II Child Special Development Institute (LPKA). This research takes the locus in LPKA Class II Jakarta. The research method uses library research (literature study) in the form of journal articles and scientific articles. Data analysis techniques used a qualitative approach, namely in the form of data reduction, data presentation and data verification (conclusion drawing). The findings and results of the research show that: (1) the implementation of learning during the Covid-19 pandemic at LPKA Class II Jakarta was carried out using the Blended Learning method, namely face-to-face (offline) and online teaching and learning activities, namely 1 session followed by 5 fostered children. take turns while adhering to health protocols. (2) the implementation of the exam is carried out online (online) using the Google meet application. (3) learning supervision during the Covid – 19 pandemic at LPKA Class II Jakarta was carried out by monitoring processes, assessments and learning outcomes.